2009
DOI: 10.3324/haematol.2008.003020
|View full text |Cite
|
Sign up to set email alerts
|

F9 Malmo, factor IX and deep vein thrombosis

Abstract: BackgroundWe recently reported the association between the Malmö sequence variant in F9 (rs6048) and deep vein thrombosis. Design and MethodsWe aimed to study whether the association between F9 Malmö and deep vein thrombosis is explained by linkage disequilibrium with nearby single-nucleotide polymorphisms, and whether the association is explained biologically by F9 Malmö affecting factor IX antigen levels or activation of factor IX. We investigated the association of F9 Malmö and 28 nearby single-nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
0
24
3
Order By: Relevance
“…4 So far, the effects of coagulant factors IX through XIII have been investigated in only a few case-control studies, including the Leiden Thrombophilia Study (LETS) 5 and, more recently, the Multiple Environmental and Genetic Assessment of risk factors for venous thrombosis (MEGA) study. 6,7 Prospective cohort studies have been lacking so far. 5 In this issue of Blood, an efficient nested case-control design has been used within LITE, a prospective cohort study in individuals aged 45 to 100 years, with a median follow-up period of more than 9 years.…”
Section: High Coagulant Factors and Venous Thrombosis -----------------mentioning
confidence: 99%
“…4 So far, the effects of coagulant factors IX through XIII have been investigated in only a few case-control studies, including the Leiden Thrombophilia Study (LETS) 5 and, more recently, the Multiple Environmental and Genetic Assessment of risk factors for venous thrombosis (MEGA) study. 6,7 Prospective cohort studies have been lacking so far. 5 In this issue of Blood, an efficient nested case-control design has been used within LITE, a prospective cohort study in individuals aged 45 to 100 years, with a median follow-up period of more than 9 years.…”
Section: High Coagulant Factors and Venous Thrombosis -----------------mentioning
confidence: 99%
“…Buil et al (2010) reported that a new locus, C4BPB/C4BPA (coding for C4-binding protein), is involved in susceptibility to VT through a still unknown, but protein S-independent mechanism. Bezemer et al (2008) found SNPs significantly associated with VT in CYP4V2/KLKB1/F11 gene cluster, as well as in the GP6 and SERPINC1 genes. Three SNPs were strongly associated with VT: rs13146272 in CYP4V2, rs2227589 in SERPINC1 and rs1613662 in GP6; 4 additional SNPs (in CYP4V2, KLKB1, and F11) were also associated with VT.…”
Section: New Approaches and Research Strategies In Inherited Thrombopmentioning
confidence: 99%
“…In contrast, functional genotypes for α-or γ-fibrinogen were not associated with fibrinogen levels, but were associated with risk of stroke; possibly because they affect not fibrinogen levels, but rather fibrin structure. Together with the report of Bezemer et al, 11 this study suggests that genetic epidemiological studies need to progress from simply assay of levels of intermediate phenotypes (e.g. coagulation factors) to inclusion of assay functions.…”
mentioning
confidence: 99%
“…Second, identification of functional genotypes which alter either factor IX levels, or factor IX function and epidemiological studies of their associations with risk of venous or arterial thrombosis: Mendelian randomization studies. 10 In this edition of Haematologica, Bezemer and colleagues 11 report a study of the Mendelian randomization approach. In a previous study of almost 20,000 potentially functional single-nucleotide polymorphisms (SNPs) for association with deep vein thrombosis (DVT), they identified an A>G sequence variant in the gene encoding factor IX (rs 6048, F9 Malmö).…”
mentioning
confidence: 99%
See 1 more Smart Citation